Technology adoption and value chains in developing countries: Panel evidence from dairy in Punjab - Saule Burkitbayeva; Emma Janssen; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2019)
The adoption of modern technologies in agriculture is crucial for improving the productivity and welfare of poor farmers in developing countries. Not much is known about how value chains do (not) affect technology transfer and/or adoption in domestic food chains in developing countries. Our paper analyzes farm-level technology adoption in the dairy chain in Punjab, India, combining quantitative panel data from representative surveys in 2008 and 2015 with data from targeted interviews with emerging modern dairy farms. Between 2008 and 2015 there were important increases in technology adoption in the form of better hygienic practices, better feed and improved livestock among traditional dairy farms. Especially those farms which lagged behind in 2008 improved their technology. However, the role of vertical coordination in value chains in stimulating technology adoption among these traditional dairy farmers seems to be minor. In contrast, we document the emergence of a group of dynamic modern dairy farms which are much larger, only use modern technology, and are fully integrated in vertically coordinated value chains which support these modern farms' management and investments.
Keywords: 330